Amygdalin and magnetic water ameliorate histological changes in liver induced by 1, 2 dimethyl hydrazine: Ahmed S. Farhan1; A. A. Thaker2 and Fadel M. Abed3 - Farhan, Ahmed S. (The Iraqi Journal of Veterinary Medicine, 2016)
This study aimed at evaluating the ameliorative effect of amygdalin and magnetic water on 1,2-dimethyl hydrazine induced toxic damage in tissues and oxidative stress in rat liver. Seven groups of ten rats each were selected for the study. Group I animals were treated as control. Group II rats received 1,2-dimethyl hydrazine (20 mg/kg body weight) injections subcutaneously once a week for 16 consecutive weeks and then kept without any treatment untill the end of the experimental period. Group III rats received amygdalin (20 mg/100 mg) daily via Oro-gastric tube. Groups IV rats were given magnetic water freely. Group V rats were given 1,2-dimethyl hydrazine + amygdalin. Group VI rat were given 1,2-dimethyl hydrazine + magnetic water Group VII rats were given 1,2-dimethyl hydrazine + amygdalin + magnetic water. Liver histological changes were studied. Degenerative changes were observed in different areas of liver tissue in 1,2-dimethyl hydrazine group, and these changes include: Fibrosis with the appearance of cell necrosis, hemorrhage, fatty infiltration and pleomorphic nuclei. While other groups showed normal appearance of the hepatic cells but some changes were observed in 1,2-dimethyl hydrazine + amygdalin + magnetic water group include: Fibrosis with the appearance of cell necrosis, hemorrhage, fatty infiltration and pleomorphic nuclei but changes in this group were less than in 1,2-dimethyl hydrazine group. In conclusion, the present results suggest that the amygdalin and magnetic water have the potential to ameliorate carcinogen 1,2-dimethyl hydrazine induced hepatotoxicity by antioxidant and antiinflammation activity.